Kinetics and Mechanism of the Oxidation Reaction of Chlorine-Containing Hydrocarbons on a Vanadium Phosphorus Catalyst - Melikova, I.G.; Efendi, A.J.; Manafov, M.R.; Aykan, N.F.; Faradjev, G.M.; Rustamova, C.T.; Shikhaliyev, N.I. (Eurasian Journal of Chemistry, 2025)
The kinetic regularities of oxidation reactions of 1,2,4-trichlorobutene-2, 2,3,3-trichlorobutene-1, 1,2,3- trichlorobutene-2 and pentachlorobutene-1 on vanadium phosphorus catalyst exhibiting high activity and selectivity were studied. The presence of parallel-sequential pathways of XY oxidation with the formation of the main organochlorine compounds and deep oxidation products was established. Ii was shown that presence and location of the double bond and the number of chlorine atoms affected the direction of the oxidation reaction. The rate of XY consumption in a fixed catalyst bed exceeds that in a fluidized bed, although the rate of formation of the target product is higher in a fluidized bed. Hypotheses reflecting the possibility of a staged reaction mechanism taking into account the modification of the surface of the vanadium-phosphorus oxide system by the main and by-products of the oxidation reactions of chlorobutenes, as well as the competition of substances for active centers were investigated. Discrimination of these hypotheses was carried out on the basis of the Bartlett’s criterion and Powell’s method, and the mechanism that most fully explains the experimental results was selected. The calculated hardness values were obtained according to the proposed kinetic model by the Kutta-Meyerson and Runge-Kutta methods. A more detailed study of the mechanism of the oxidation reaction of chlorinated hydrocarbons will allow for effective control of its course and the achievement of selective oxidation of chlorinated hydrocarbons.
Keywords: kinetic regularities; mechanism; vanadium-phosphorus catalyst; oxidation reactions; chlorinated hydrocarbons; product formation rate; fluidized bed; fixed catalyst bed; Bartlett’s criterion